2019
DOI: 10.1038/s41433-019-0495-y
|View full text |Cite
|
Sign up to set email alerts
|

A trial of a mechanical device for the treatment of blepharospasm

Abstract: Background Idiopathic blepharospasm (IB) is a rare but well-characterised adult onset focal dystonia that may cause severe visual disability. The most effective treatment is with periodic injections of botulinum toxin (BTX) into the pre-tarsal and/or pre-septal orbicularis oculi muscles bilaterally. However, even with treatment, practical visual function often remains compromised. A subset of IB sufferers find that eye opening improves with a focal unilateral digital pressure usually on a specific point on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Kilduff et al (22) and Loyola et al (6) observed that patients with hemifacial spasm also benefit from these alleviating maneuvers. Although little is known regarding the mechanism, sensory tricks act as relieving factors for the spasms (6,22,23) . Several sensory tricks have been described (6,22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kilduff et al (22) and Loyola et al (6) observed that patients with hemifacial spasm also benefit from these alleviating maneuvers. Although little is known regarding the mechanism, sensory tricks act as relieving factors for the spasms (6,22,23) . Several sensory tricks have been described (6,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Local compression is one of the most frequently described tricks and was reported by 34.3% of our patients. Fantato et al (23) , based on local compression as an alleviating maneuver for eyelid spasms, conducted a study that demonstrated an adjuvant effect of a simple spectaclemounted device (Pressop) in those with essential blepharospasm. In our study, 47% of patients reported using a sensory trick.…”
Section: Discussionmentioning
confidence: 99%